Optimalization of trails tours in Pinge Tourism Village to improve the community's economy during the Covid-19 pandemic - Mahendra, I Wayan Eka; Supartini, Ni Luh; Suwintari, Gusti Ayu Eka; Sulasmini, Ni Made Ayu; Parwati, Komang Shanty Muni (Community Empowerment, 2021)
Pinge Village is the first tourist village in Tabanan Regency which was officially inaugurated by Tabanan Regent Decree No. 337 of 2004 that concerning to Design Pinge Traditional Village as a Tourism Village. This village has several potentials as sources of attractions for tourists. These potentials include beautiful natural scenery, cool air, residential traditional housing, friendly people, and characteristics of rural tourism in the form of "trails" along village roads. The existing potential has not been managed optimally due to several obstacles, such as: 1) the English language skills of local tour guides are still low, especially the mastery of English vocabulary and 2) the management of homestays is not optimal, because most of the tourist activities are served by travel agents. This problem was overcome through 16-hour English short course activities, 8-hour guided mentoring, and comparative studies. As a result, the implementation of the English short course received positive responses from the participants, the village head, the manager of the Pinge Tourism Village, and the head of the Pokdarwis Pinge Asri. Statistically, there was an increase in participants' English proficiency by 22.14%. Mentoring and comparative studies on homestay management also received positive responses, even the homestay managers want this activity to be carried out continuously.